Resilience of the nursing team in the hospital scope with emphasis on the pandemic COVID-19 (Research, Society and Development, 2020)
Nursing is faced and coexists, in daily life, with numerous stressors, internal and external, which compromise health, quality of life, interfere in professional performance and can put the safety of assistance to the population at risk. This research aims to analyze in the literature scientific evidence on the resilience of nursing professionals in the hospital, as a subsidy for carrying out actions, and educational and health-promoting interventions to prevent their illness, including for better coping with the pandemic COVID-19, maintaining the quality of life, assistance to patients, health institutions and society. It is an integrative review of articles published in the last 10 years and indexed in the Web of Science, PubMed and Virtual Health Library databases (Medline, SciELO, Lilacs). 15 full articles were evaluated. Four analytical categories were established: “Characterization of scientific evidence”; “Personal, environmental and cultural aspects involved in the resilience of Nursing and in facing the pandemic”; "Risk factors for illness and resilience", and" Nursing resilience and interference in hospital care for individuals in psychological distress and in the death process". The physical and mental suffering of Nursing has been perpetuated and worsened during the pandemic. Knowing the illness profile of the worker and the characteristics of the work environment is a important condition, it allows accurate situational diagnosis, recognition of risk factors and establish strategies aimed at improving working conditions, quality of life and reducing occupational illness.